Oxidation of Bovine Albumin by Hypochlorous and Hypobromous Acids: Structural and Functional Alterations - Petrônio, Maicon Segalla [UNESP]; Fernandez, João Roberto [UNESP]; menezes, Manoel Lima de [UNESP]; Ximenes, Valdecir Farias [UNESP] (My University, 2013)
Aims: Hypochlorous (HOCl) and hypobromous (HOBr) acids are among the most powerful oxidants produced by the innate immune cells. Albumin is the predominant protein in most body fluids and is considered the most important antioxidant of blood plasma. Study Design: Oxidation of bovine albumin (BSA) and study of its structural and functional alterations. Place and Duration of Study: Faculty of Science and Faculty of Pharmaceutical Science, University of the State of Sao Paulo UNESP, between June and December 2012. Methodology: BSA was oxidized with excess of HOCl or HOBr and its structural and functional alterations were analyzed by spectroscopic techniques as UV-Vis absorption, intrinsic and synchronous fluorescence, fluorescence quenching, Rayleigh scattering and circular dichroism. Results: Both oxidants were able to deplete the intrinsic fluorescence of BSA, but HOBr was more effective than HOCl. The alterations in the synchronous fluorescence, UV-Vis absorption, and the appearance of a fluorescence band centered at 450 nm confirmed the difference between the oxidants. The oxidation did not induce aggregation of BSA as measured by Rayleigh scattering. The far-UV circular dichroism spectra showed a loss in the helical content and the near-UV-circular dichroism showed an alteration in the tertiary structure; HOBr was the more effective of the oxidants in this case. However, the oxidations did not induce significant alterations in the binding capacity of BSA, which was evaluated using hydrophobic (norfloxacin) and hydrophilic (ascorbic acid) drugs. Conclusion: These results suggest that, although highly susceptible to oxidation, the alterations did not inhibit BSA’s physiological function as a transport protein.
Keywords: Hypochlorous acid; Hypobromous acid; Albumin; Oxidative stress; Binding capacity